Effectiveness of granulocyte colony-stimulating factor for patients with acute-on-chronic liver failure: a meta-analysis - Huang, Wei; Ma, Yuanji; Du, Lingyao; Kang, Shuang; Liu, Chang-Hai; Bai, Lang; Lei, Xuezhong; Tang, Hong (Annals of Saudi medicine, 2021)
The safety and efficacy of granulocyte colony-stimulating factor (G-CSF) for the treatment of acute-on-chronic liver failure (ACLF) remain uncertain. Therefore, we conducted a meta-analysis to draw a firmer conclusion. We searched the Cochrane library, PubMed, Embase, and China Biology Medicine disc to identify relevant RCTs performed before January 2020. Risk ratios (RRs) and their 95% confidence intervals (95% CIs) were calculated using a random effects model. RRs (95% CI) for 1-, 2-, and 3-month survival rates. Six RCTs, including three open-label studies. The six studies included 246 subjects (121 in a G-CSF group and 125 in a control group). G-CSF administration significantly improved the 1-, 2-, and 3-month survival rates in patients with ACLF. The pooled RRs (95% CI, P) were 0.43 (0.27-0.69, =.0004), 0.44 (0.32-0.62, <.00001), and 0.39 (0.22-0.68, =.0009), respectively. G-CSF may be beneficial and effective in the treatment of ACLF, but further studies are needed to verify this conclusion. The sample size was small, and studies were restricted to countries in Asia. CRD42021225681 CONFLICT OF INTEREST: None.